THE RELATIONSHIPS BETWEEN THE PROVIDING OF SELF-PROTECTIVE EQUIPMENTAND OCCUPATIONAL STRESS EVENTS OF HEALTH OFFICERS IN THE HANDLING OF COVID-19 IN KANDAI HEALTH CENTER: SELF-PROTECTIVE EQUIPMENT AND OCCUPATIONAL STRESS - Noviati Noviati; Sitti Marya Ulva (STIKes Mandala Waluya Kendari, 2022)
Background: The corona virus (covid-19) pandemic in Indonesia is still growing. Every week the number of infections of Covid-19 was 2,273 cases. Where as, 198 of them died and 164 people were treated. In fact, among them are healthy workers who help treat corona virus patients and become infected afterward. There was a shortage of personal protective equipment (PPE) for health workers in Southeast Sulawesi province, especially at Kendari City, Health Center Kandai. This makes health workers have to take turns wearing PPE if they want to do their job. Therefore, many health workers feel restless and do not want to carry out their duties if they are not provided with adequate PPE, because they will examine people or patients whose health status is not yet known. The purpose of this study is to analyze the relationship between the providing of self-protective equipment and occupational stress events of health officers in the handling of Covid-19 at Kandai health center. Methods: This type of research is an analytic study with a cross-sectional approach. The sample in this study amounted to 58 people using the total sampling method. Results: The results showed that there was a relationship between the provision of Personal Protective Equipment (PPE) with the incidence of work stress for health workers in handling covid-19 at Kandai Health CenterKendari City, with the statistical test results being 18,322. Conclusion: It is hoped that policy makers, especially the head of the Kandai Health Center, pay more attention to the safety and health of their employees, such as in the provision of PPE, and for health workers, especially at Kandai Health Center, to further improve the Covid-19 protocol that is applied to themselves and patients.